The effects of lighting conditions and food restriction paradigms on locomotor activity of common spiny mice, Acomys cahirinus - Chabot Christopher C; Connolly Devin M; Waring Brenda B (Journal of Circadian Rhythms, 2012)
Abstract Background An endogenous circadian clock controls locomotor activity in common spiny mice (Acomys cahirinus). However, little is known about the effects of constant light (LL) on this activity or about the existence of an additional food entrainable clock. A series of experiments were performed to investigate the effects of LL and DD on tau and activity levels. Methods Spiny mice were housed individually and their running wheel activity monitored. One group of mice was exposed to LD, DD and several intensities of LL. Another group was exposed to a restricted feeding (RF) paradigm in light: dark (LD) during one hour before the L to D transition. Significance of rhythmicity was assessed using Lomb-Scargle periodograms. Results In LD all animals exhibited nocturnal activity rhythms that persisted in DD. When animals were exposed to RF (during L), all of these animals (n = 11) demonstrated significant food anticipatory activity as well as an increase in diurnal activity. This increase in diurnal activity persisted in 4/11 animals during subsequent ad libitum conditions. Under LL conditions, the locomotor rhythms of 2/11 animals appeared to entrain to RF. When animals were exposed to sequentially increasing LL intensities, rhythmicity persisted and, while activity decreased significantly, the free-running period was relatively unaffected. In addition, the period in LL was significantly longer than the period in DD. Exposure to LL also induced long-term changes (after-effects) on period and activity when animals were again exposed to DD. Conclusions Overall these studies demonstrate clear and robust circadian rhythms of wheel-running in A. cahirinus. In addition, LL clearly inhibited activity in this species and induced after-effects. The results also confirm the presence of a food entrainable oscillator in this species.